2023
DOI: 10.1002/chem.202301290
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Crystalline Intermediates in Mechanochemical Cyclorhodation Reactions Elucidated by in‐Situ X‐ray Powder Diffraction and Computation

Abstract: The occurrence of crystalline intermediates in mechanochemical reactions may be more widespread than previously assumed. For example, a recent study involving the acetate‐assisted C–H activation of N‐heterocycles with [Cp*RhCl2]2 by ball milling revealed the formation of transient cocrystals between the reagents prior to the C–H activation step. However, such crystalline intermediates were only observed through stepwise intervallic ex situ analysis and their exact role in the C–H activation process remained un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Such a perspective would be consistent with the emergent realisation that self-assembled solid-state complexes, such as cocrystals, can play an important role as intermediates in mechanochemical reactions. 57–59…”
Section: Resultsmentioning
confidence: 99%
“…Such a perspective would be consistent with the emergent realisation that self-assembled solid-state complexes, such as cocrystals, can play an important role as intermediates in mechanochemical reactions. 57–59…”
Section: Resultsmentioning
confidence: 99%
“…Interest in the mechanochemical synthesis and reactivity of coordination and organometallic complexes has also experienced recent growth. 3 a – c ,10 d , j ,26 We previously reported that rhodacyclic complexes of the types 3 or 6 can be generated efficiently under ball milling conditions and that they are competent precatalysts for oxidative C–H methylation. 8 h Under ‘grind-and-heat’ conditions, rhodacycle 3a (X = Cl) formed in 28% yield from 1a and [Cp*RhCl 2 ] 2 (see Table S1†).…”
Section: Resultsmentioning
confidence: 99%
“…Herna ´ndez et al 40 reported that in situ analysis of the ball milling of mixtures of 1 and 2 yielded the 4a cocrystal after 3 minutes and the 4b cocrystal after 18 minutes, then the two phases coexisted for about 20 minutes gradually exhausting 4a so that after about 40 minutes only 4b remained. (For in situ monitoring of mechanochemical reactions, see ref.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, similar crystalline intermediates were detected before the C-H activation step in mechanochemical cyclorhodations of substrates different from BHQ such as phenylpyridine and 2-phenylquinoline. 37 In order to understand why 4a is the first cocrystal produced by the milling and why only 4b seems to lead to 5, we took the reported Cartesian coordinates of all needed species from the above cited experimental works 37,40 and proceeded with two alternative approaches: first, we relaxed the reported crystal geometries to locate the nearest equilibrium structure and to optimize the lattice parameters under periodic boundary conditions and then calculated all reactivity indices on the extended solids (we call this the extended solid approach), second, we took the structures of the rhodium dimer 1 (Rc) and of the 2Rc + 3BHQ fragment within the 4a and 4b optimized crystals (Fig. 2) and calculated the reactivity indices (we call this the cluster approach).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation